Sosialisasi Hukum Keluarga Islam untuk Masyarakat Pedesaan: Meningkatkan Kesadaran dan Pemahaman melalui Pendekatan Komunitas - Abdurrahman Hakim; Suci Ramadhan; Andri Setiawan (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
This article aims to explore the importance of socialization of Islamic family law for rural communities, with a focus on increasing awareness and understanding through a community approach. This study uses the Community Participation method involving qualitative and quantitative approaches. Data were collected through surveys, in-depth interviews, and focus group discussions (FGDs) with community members, religious leaders, and legal facilitators. Academic debates surrounding the implementation of Islamic family law in rural areas often involve views on the differences in understanding between legal texts and existing social practices. Some scholars argue that the community's ignorance and misunderstanding of this law causes conflict in households, while others emphasize the importance of integrating local values ​​with Islamic law for the effectiveness of socialization. The results of the study indicate that a community-based approach, including training and workshops, was successful in increasing community awareness of rights and obligations under Islamic family law. In addition, active community participation in the socialization process increased their understanding of family law issues, which in turn could reduce potential conflicts and strengthen social structures in rural communities.